IN VITRO ANTI-INFLAMMATORY ACTIVITY OF THE COMPONENTS OF AMOMUM TSAO-KO IN MURINE MACROPHAGE RAW 264.7 CELLS - Choi, Chun Whan; Shin, Ju Young; Seo, Changon; Hong, Seong Su; Ahn, Eun-Kyung; Jung, Young Hoon; Oh, Joa Sub (African Journal of Traditional, Complementary and Alternative Medicines, 2018)
Background: Plants still remain the prime source of drugs for the treatment of inflammation and can provide leads for the development of novel anti-inflammatory agents. Material and methods: An in vitro bioassay guide revealed that the 80% ethanol (EtOH) extract of the whole plant, Amomum tsao-ko (Zingiberaceae), displayed anti-inflammatory activity after assessing its effects on murine macrophage RAW 264.7 cells. Result: Phytochemical study of the 80% EtOH extract of Amomum tsao-ko led to the isolation of eight compounds: 4-hydroxy-3-methoxy-benzoic acid (1), meso-hannokinol (2), (+)-hannokinol (3), coumaric acid (4), 4-hydroxy-benzoic acid (5), (+)-epicatechin (6), (-)-catechin (7), and myrciaphenone A (8). The results indicated that two of the isolated components, (+)-epicatechin (6) and (-)-catechin (7), inhibited the production of nitric oxide (NO) significantly in lipopolysaccharide treated RAW 264.7 cells. Conclusion: LPS-induced interleukin tumor necrosis factor-alpha (TNF-), IL-1β and IL-10 production was also decreased in a dose-dependent manner. In addition, western blot analysis revealed that (+)-epicatechin (6) and (-)-catechin (7) reduced the expression of inducible nitric oxide synthase and inhibited nuclear localization of nuclear factor kappa-B (NF-κB).